(untitled) (Journal of Environmental Science and Natural Resources, 2016)
The growth performance of Macrobrachium rosenbergii (Deman,1879) under different stocking densities was conducted under three treatments each with three replications namely T1: 10m-2 T2: 12m-2; T3: 14m-2 for a period of six months from April to September, 2012 in 9 experimental ponds in Terokhada Upazilla under Khulna district. Supplementary feeds (mustard oil cake (20%), wheat bran (20%), rice bran (20%), fish meal (25%) and maize bran(15%) were used for all stocked individual. Water quality parameters and growth performances were monitored monthly. The mean values of water temperature, transparency, dissolve O2, pH and salinity were varied from 28.88 ± 0.161±oC(T2) to 31.32 ± 0.97±oC (T1), 29.73 ± 0.34cm(T1) to 32.70 ± 0.28cm(T2), 5.33 ± 0.184mg-1(T3) to 6.17 ± 0.13 mg-1 (T1), 6.52 ± 0.205(T2)to 6.79 ± 0.18(T1) and 13.75 ± 0.16(T2) to 15.22 ± 0.20(T1). The weight gain of Macrobrachium rosenbergii were 59.79± 0.15 g(T1), 50.86±0.14g(T2),48.78±0.12g(T3).The survival rate (%) of M. rosenbergii were 75.02±0.577 (T1), 66.66±0.88 (T2), 61.01±0.577(T3) respectively. Yields (Kg ha-1 6 month-1) Macrobrachium rosenbergii were 2302.04kg (T1), 1768.52 kg (T2), 1393.808 kg (T3) respectively. Total cost 656000 ± 17480 Tk ha-1 (T1), 596120 ± 4520 Tk ha-1 (T2) and 549100 ± 9440 Tk ha-1 (T3) respectively and total return of different treatments T1, T2 and T3 were 1492400 ± 12800 Tk ha-1, 1078200 ± 11930 Tk ha-1 and 806480 ± 9190 Tk ha-1 respectively. Net benefit were 801900 ± 7340 Tk ha-1, 49400± 5930 Tk/ha and 288600 ± 13240 Tk ha-1 in T1, T2, T3 treatments respectively. From these findings, it could be concluded that highest yield was achieved from T1 and lowest in T3 which was significantly (P<0.05) different among the treatments where stocking density were less than other treatments. J. Environ. Sci. & Natural Resources, 9(1): 53-57 2016